A note on the theorems of paley and stein - Kirillov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We show that, under the conditions of the theorems of Paley and Stein, a system with bounded norms in L_∞ can be replaced by a system with bounded norms in the space of functions of bounded mean oscillation.